Identifying Core Linguistic Factors for Effective Writing: Basis for the Development of Contextualized Activities for Grade V Learners - Resayaga, Kathrine Mae (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the core linguistic factors affecting the writing proficiency of Grade V learners and developed, validated, implemented, and evaluated contextualized writing activities under Project WRITE. Anchored on Sociocultural Theory, Contextual Learning Theory, and Process Writing Theory, the study employed a Research and Development (R&D) design combined with a quasi-experimental pretest-posttest approach. The respondents included 72 Grade V learners from Bonga Elementary School in Ligao City, Albay. Based on the diagnostic assessment, 11 learners identified under the Low Mastery level participated in the intervention phase. Data were collected using the Linguistic Factors Writing Test and the DepEd Learning Resource Evaluation Form (LR Form No. 2A). Findings revealed that learners performed strongest in discourse competence, while lexicon emerged as the weakest linguistic factor, followed by sentence structure and syntax and grammar. The results indicated uneven development across the identified linguistic components, particularly among learners classified under the Low Mastery level. These findings served as the basis for the development of Project WRITE, which consisted of contextualized writing activities supported by a Learner’s Module and Teacher’s Guide. Following implementation, learners demonstrated improvements in lexicon, sentence structure, syntax and grammar, and discourse competence. The developed instructional materials were evaluated by teachers and language experts and received Very Satisfactory ratings in terms of content, format, presentation and organization, and accuracy and up-to-datedness, indicating their suitability for classroom use. The study concluded that contextualized writing activities can effectively improve the writing proficiency of Grade V learners by addressing identified linguistic weaknesses and providing meaningful learning experiences. The findings support the integration of contextualized writing instruction and the continued development of validated instructional materials to enhance literacy outcomes in elementary education. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities) by promoting inclusive literacy development through context-responsive instruction. It contributes to educational, institutional, and socio-economic sustainability by strengthening learners’ communication skills and supporting evidence-based classroom practices.
Keywords: Contextualized Writing Activities; Discourse Competence; Grade V Learners; Lexicon; Project WRITE; Sentence Structure; Syntax and Grammar; Writing Proficiency